In-vitro degradation and corrosion protection of chitosan composite coatings containing hydroxyapatite or bioactive glass on Ti6Al4V implants: A comparative study - Azari, Rezvan; Saqib, Muhammad; Carrasco, Ivan Lopez; Ficai, Anton; Opitz, Joerg; Beshchasna, Natalia; Boccaccini, Aldo R. (Surface & Coatings Technology, 2026)
This research systematically evaluates the biodegradation and corrosion behavior of a novel class of composite coatings for bone implants based on chitosan (CS) and two bioactive components (Hydroxyapatite (HA) and Bioactive glass (BG)) in simulated physiological conditions through a comparative approach. Chitosan (CS)-based composite coatings (HACS and BGCS) were deposited on Ti6Al4V substrates via electrophoretic deposition (EPD) using unified processing parameters. Initially, the primary materials, relevant suspensions, and final coatings were studied and compared by scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), Zetasizer, and X-ray diffractometer (XRD) methods. While positive ZPs for both HACS (55.44 ± 2.43 mV) and BGCS (35.62 ± 2.95 mV) suspensions were aligned with cathodic deposition of coatings, a large difference between recorded current densities during EPD for HACS (6.98 ± 0.38 mA·cm−2) and BGCS (56.14 ± 3.99 mA·cm−2) were noteworthy. The in-vitro degradation of BGCS and HACS coatings in DMEM solution was assessed not only under a conventional static condition but also within a fluid-dynamic degradation setup. The mass and pH evolution, surface morphology, compositional changes, and release of metallic ions were investigated over the degradation period by gravimetric, optical microscope, SEM, FTIR, and ICP-MS techniques, respectively. While the majority of BGCS degradation (above 3 mg·cm−2) occurred only after 8 h of immersion, a maximum mass loss of about 2 mg·cm−2 happened for HACS coatings on day 10 of the test. Electrochemical corrosion studies of coated samples compared to plain substrates in DMEM solution were carried out using open circuit potential (OCP), potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS) tests, and the equivalent circuit was defined to model the experimental data. Interestingly, the corrosion rate of the uncoated sample (9.13E−05 mm·year−1) was about three times and ten times less than HACS and BGCS samples, respectively. It was revealed that the surface pretreatment (polishing) method can have a decisive effect on the corrosion protection behavior of Ti6Al4V samples, coated with CS-based EPD coatings.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Bioactive glass; Chitosan; Corrosion; Degradation; Electrophoretic deposition (EPD); Hydroxyapatite